Parent perspectives and reasons for lower urgency paediatric presentations to emergency departments. (15th February 2016) - Freed, Gary L; Allen, Amy R; Turbitt, Erin; Nicolas, Caroline; Oakley, Ed
Abstract: Objective: The age band with, by far, the greatest number of ED presentations is children 0–4 years, with other paediatric age bands also among the highest. As the majority of these presentations are for lower urgency conditions, we sought to determine why parents seek ED care for their child for lower urgency conditions. Methods: A survey study of 1150 parents or guardians of children with lower urgency conditions (triage category 4 or 5) presenting to the EDs of three public general and one paediatric specialty hospital in metropolitan Melbourne. Results: Fewer than half of parents (43%) attempted to make an appointment with a general practitioner (GP) for their child prior to presenting to the ED. Two‐thirds of those who did contact a GP were instructed by their GP to go to the ED for their lower urgency condition. Few attempted to contact a nurse telephone triage service or after‐hours GP service. Conclusions: The current magnitude and the growth of lower urgency paediatric ED presentations is a strain on the health care system. Efforts to educate parents regarding the suitability and availability of GP appointments can be the cornerstone of an initial strategy to address this issue. However, efforts to address the high rates of GP referral to EDs for low urgency presentations will be more vexing to develop, yet no less important. They will require addressing fundamental issues in both current GP care for children and the training of GP registrars.